1998
DOI: 10.1097/00006254-199808000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Outcome of Laparoscopic Ovarian Drilling for Polycystic Ovarian Syndrome in Women With Anovulatory Infertility

Abstract: Objective To describe and analyse the factors affecting the pregnancy rate of laparoscopic ovarian drilling for polycystic ovarian syndrome in women with anovulatory infertility. Design A retrospective study. Setting A specialist infertility clinic based at a teaching hospital in England. Population One hundred and eighteen women, for whom hospital records and follow up data were available, with polycystic ovarian syndrome who underwent laparoscopic ovarian surgery for anovulatory infer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
3
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 0 publications
1
11
3
2
Order By: Relevance
“…We do not know whether the women who undergo ovarian interstitial laser treatment will have recurring clinical or hormonal problems, but because of a minimal surface damage of the ovaries, it is possible that ovarian interstitial laser treatment can be an improved surgical approach to restore ovulation with a minimal risk of adhesion formation in women with PCOS who are CC resistant or unresponsive to hormone therapy. Several previous studies have shown electrocautery to be superior to laser for LOD in terms of safety, simplicity, effectiveness and costs; 5,16,17 however, interstitial therapy is greatly superior to electrocautery or LOD in safety, simplicity and costs and in our experience is at least equal in effectiveness.…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…We do not know whether the women who undergo ovarian interstitial laser treatment will have recurring clinical or hormonal problems, but because of a minimal surface damage of the ovaries, it is possible that ovarian interstitial laser treatment can be an improved surgical approach to restore ovulation with a minimal risk of adhesion formation in women with PCOS who are CC resistant or unresponsive to hormone therapy. Several previous studies have shown electrocautery to be superior to laser for LOD in terms of safety, simplicity, effectiveness and costs; 5,16,17 however, interstitial therapy is greatly superior to electrocautery or LOD in safety, simplicity and costs and in our experience is at least equal in effectiveness.…”
Section: Discussionmentioning
confidence: 46%
“…Laparoscopic ovarian diathermy or drilling (LOD) has been used in the management of anovulatory women with clomifene‐citrate(CC)‐resistant polycystic ovary syndrome (PCOS) for the past two decades. With ovulation rates of 70–80% and pregnancy rates of 30–60% within 6–12 postoperative months, the effectiveness of LOD has been well documented in the literature 1–8 . However, about 20–30% of women fail to respond to LOD, and about 50% of those who initially respond to the treatment became anovulatory again after a few months 1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This simple procedure appears to be particularly useful for outpatient microlaparoscopies, in which the average discharge time is 2 to 3 h after the operation. The effect of local anesthesia is temporary; however, this approach allows the possibility of a quicker discharge at 2 h after surgery [19][20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic ovarian electrocautery (LOE) is an alternative treatment for PCOS women who are clomiphene citrate-resistant [12] . Ovarian wedge resection is the forerunner of LOE which was first introduced by Stein and Leventhal [13] for women with PCOS.…”
Section: Introductionmentioning
confidence: 99%